Network recovery protection and restoration of optical, SONET-SDH, IP and MPLS - Vasseur, Jean-Philippe.; Pickavet, Mario; Demeester, Piet. (San Francisco, Calif. : Morgan Kaufmann, 2004)
Network Recovery is the first book to provide detailed information on protecting and restoring communication networks, and it sets a sky-high standard for any that may follow. Inside, youll learn specific techniques that work at each layer of the networking hierarchyincluding optical, SONET-SDH, IP, and MPLSas well as multi-layer escalation strategies that offer the highest level of protection. The authors begin with an incisive introduction to the issues that define the field of network protection and restoration, and as the book progresses they explain everything you need to know about the relevant protocols, providing theoretical analyses wherever appropriate. If you work for a network-dependent organization, large or small, youll want to keep Network Recovery within reach at all times. * Shows you how to implement protection and recovery techniques that will save your organization time and money. * Documents techniques for the optical, SONET-SDH, IP, and MPLS layers, as well as multi-layer escalation strategies. * Shows you how to evaluate these techniques in relation to one another, so you can develop an optimal network recovery design. * Provides industry examples and simulation results. * Delves into the inner workings of relevant protocols and offers theoretical analyses wherever this information contributes to your practical knowledge.
SONET/SDH networks -- Optical networks -- IP routing -- MPLS traffic engineering recovery mechanisms -- Multilayer networks.
Includes bibliographical references (p. 479-489) and index.
Keywords: Computer networks -- Management; Telecommunication -- Traffic; MPLS standard; SONET (Data transmission); TCP/IP (Computer network protocol); Electronic books